The Egg-Stepping Tradition in Javanese Marriage Customs from the Perspective of Islamic Law - Mansurudin Mansurudin; Ecep Ishak Fariduddin (Transpublika Publisher, 2026)
Marriage is one of the most important events in human life. One of the ceremonies that demonstrates the harmonious blend of Javanese traditional weddings is the egg-stepping tradition. This study examines the permissibility (ḥukm) of the egg-stepping tradition within Javanese marriage from the perspective of Islamic legal principles, assessing its alignment with the Compilation of Islamic Law (KHI) and broader sharīʿah objectives. This study employed a qualitative method with a normative juridical analysis. The normative juridical approach, a key technique in legal research that stresses the examination of legal norms, doctrines, and principles, is used in this study. From the perspective of the Compilation of Islamic Law (KHI), the egg-stepping practice can be regarded as acceptable, provided that marriage is carried out in accordance with Islamic principles and that local customs do not conflict with sharia. Therefore, the egg-stepping tradition is not a problem, as long as it does not violate Islamic law. On the other hand, the egg-stepping ritual forms part of the symbolic sequence in Javanese traditional weddings, carrying deep philosophical meaning and cultural significance. Such customs reinforce the normative view that marriage is designed to establish a family, as outlined in the Marriage Law (Law No. 1 of 1974, amended by Law No. 16 of 2019). Consequently, these traditions may influence judicial interpretations, embedding communal values into legal reasoning. Future research could use qualitative methods to explore contemporary Indonesian ulama’s views on these traditions, addressing the community’s need for contextualized fatwa guidance.